Frase Preposisi Bahasa Jawa Dialek Brebes: Analisis X-Bar (Kajian Sintaksis) - Hermawan, Didi; Purwaningsih, Tinah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Brebes has at least two languages, namely Javanese and Sundanese Brebes. The study focuses on the Javanese language Brebes dialect. The language has many markers; preposition marker is one of them. There were several investigations regarding the language using a structural approach. The aim of this paper is to figure out the internal structure of preposition phrases (PP) in Javanese language dialect. FP structure was analyzed using X-bar theory; a theory which examines the internal structure of the phrase. The research data was obtained from native speakers of Javanese language Brebes dialect. The result of the research indicates that the Javanese language Brebes dialect PP construction is formed by a complement (Comp), a modifier (Mod) , and a specifier (Spec). These are the rules (1) FP = P', Spec.; P '= P, Comp., (2) FP = P', Spec.; P '= P', Mod.; P '= P, Comp., (3) FP = P', Spec.; FP = P ', Spec.; P '= P', Mod.; P '= P, Comp.